Placental and colostral transfer of antibodies reactive with enteropathogenic Escherichia coli intimins α, β, or γ, - Silvia P.N. Altman; Milene Tino-; Cristiane B. Carbonare; Patricia Palmeira; Solange B. Carbonare
Abstract Objective: Intimins are protein adhesins of enteropathogenic Escherichia coli and enterohemorrhagic E. coli capable of inducing attachment and effacement lesions in enterocytes. Anti-intimin antibodies are important for the protection from enteropathogenic E. coli and enterohemorrhagic E. coli infections because these antibodies inhibit bacterial adhesion and impair the initial step of the pathogenesis. We studied the transfer of maternal anti-intimin antibodies from healthy Brazilian mothers to their newborns through the placenta and colostrum. Methods: Serum immunoglobulin G and secretory immunoglobulin A antibodies against conserved and variable regions of intimins α, β, and γ were analyzed using an enzyme linked-immunosorbent assay in the blood and colostrum from 45 healthy women as well as cord blood serum samples from their newborns. Results: The concentrations of antibodies reactive with α intimin were significantly lower than those of anti-γ and anti-conserved intimin antibodies in the colostrum samples. IgG serum antibodies reactive with all the subtypes of intimins were transferred to the newborns, but the concentrations of anti-conserved intimin serum antibodies were significantly higher in mothers and newborns than concentrations of antibodies against variable regions. The patterns of IgG transfer from mothers to newborns were similar for all anti-intimin antibodies. These values are similar to the percentage transference of total IgG. Conclusions: Anti-intimin antibodies are transferred from mothers to newborns through the placenta, and reinforce the protection provided by breastfeeding against diarrheagenic E. coli infections.